Bildung für nachhaltige Entwicklung - Impulse zu Digitalisierung, Inklusion und Klimaschutz - Eberth, Andreas; Goller, Antje; Günther, Julia; Hanke, Melissa; Holz, Verena; Krug, Alexandria; Rončević, Katarina; Singer-Brodowski, Mandy (Schriftenreihe "Ökologie und Erziehungswissenschaft" der Kommission Bildung für nachhaltige Entwicklung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2022)
How can the relationship between Education for Sustainable Development (ESD) and other defining social issues such as social inequality, inclusion and digitalisation be determined? The authors present well-founded overviews as well as current empirical research from various academic disciplines on these and other aspects of ESD.